HUBUNGAN KONDISI MENTAL EMOSIONAL DENGAN PERKEMBANGAN ANAK PRASEKOLAH DI WILAYAH RW 05 KELURAHAN SETU - Dianah Syahirah (2022)
The preschool period is a golden age because children already have sensitivity to the stimuli they receive. The stage of growth and development at this time will affect the conditions for further development. This study aims to determine the corelation of mental emotional conditions with the development of preschool in area of RW 05 Setu Village. The method used in this research is descriptive analytic with a cross sectional approach. The sampling technique used Probability Sampling by using proportional random sampling to obtain as many as 90 mothers with preschool aged 4-6 years. The sample of this study were mothers and children who met the inclusion and exclusion criteria. This study used the Somers'd test and the results showed that there was a significant correlation between mental emotional conditions and child development with a p value of 0.000 (<0.05). This research is expected to give mothers insight and knowledge related to children's emotions and child development so that they are able to understand emotional mental changes and proper child development so that children's development will be optimal.